Traditional food security and food sovereignty in the coastal region of South-Central Alaska - Joseph Nyholm; Amanda Walch; Leslie Redmond (International Journal of Circumpolar Health)
A food assessment questionnaire was completed by Alutiiq and Eyak peoples of the Chugach Region of Alaska in 2016–2017. This questionnaire, conducted by the Chugach Regional Resource Commission, gathered 87 responses from adults residing in seven communities. The questions related to traditional food systems, food security, and food sovereignty and were organised into six sections: Community Food Resources, Diet and Health, Culture, Organisation and Governance, Food Resources, and Natural Resources and Environment. Nine questions directly addressed food sovereignty. Results revealed the importance of traditional food sources in the communities, foods that are not readily available or are difficult to access, resources that are useful to improve traditional food security, health problems that are perceived to be caused or exacerbated by the lack of traditional foods in the area, traditional foods commonly consumed, and barriers from accessing traditional foods. Additionally, recommendations for improving food systems and addressing barriers are provided.